Risk factors of de novo hepatitis B virus infection in pediatric hepatitis B core antibody positive liver graft recipients under prophylactic therapy. Issue 5 (24th October 2019) - Dong, Chong; Song, Zhuolun; Chen, Jing; Ma, Nan; Meng, Xingchu; Sun, Chao; Duan, Keran; Bi, Bowen; Wang, Kai; Qin, Hong; Han, Chao; Yang, Yang; et al.
Abstract: Background and Aim: We aim to investigate the risk factors of de novo hepatitis B virus (HBV) infection in pediatric liver transplantation recipients receiving hepatitis B core antibody positive grafts and to evaluate the efficacy of our prophylactic strategies. Methods: One hundred thirty‐nine pediatric recipients receiving hepatitis B core antibody positive grafts operated from September 2016 to September 2018 were retrospectively enrolled, and all the patients received prophylactic treatment to prevent de novo HBV infection. Donor and recipient features, operative information along with graft, and recipient outcomes were compared between recipients with or without de novo HBV infection. Univariate and multivariate analyses were applied to identify the risk factors of de novo HBV infection. Results: The mean follow‐up time was 23.5 ± 15.7 months, and the overall incidence of de novo HBV infection was 3.6%. Recipients with de novo HBV infection showed equal graft and recipient outcome compared with the recipients without de novo HBV infection during the follow‐up time. Recipient preoperative hepatitis B surface antibody titer of < 1000 IU/L (odds ratio [OR] = 9.652, P  = 0.024), graft HBV DNA of > 1000 copies (OR = 9.050, P  = 0.032), and intraoperative fresh‐frozen plasma transfusion of > 400 mL (OR = 10.462, P  = 0.023) were identified as independent risk factors for de novo HBV infection. Conclusion: Hepatitis B core antibody positive grafts can safely be used in pediatric liver transplantation under rational prophylactic therapy.